Nucleic acid assay system for tier II labs and moderately complex clinics to detect HIV in low-resource settings - Tang, Wen (2010)
There is a clear need for an instrument-free molecular diagnostic system for detecting HIV-1 RNA or DNA that can be used in developing countries. Such a test could find utility in the early diagnosis of HIV-1 infection in infancy, as well as serve as a surrogate end-point for vaccine trials. We have developed an IsoAmp® HIV-1 assay (BioHelix Corp, Beverly, MA) targeting the HIV-1 gag gene using our isothermal reverse transcription helicase dependent amplification chemistry (RT-HDA). This IsoAmp® HIV assay uses a disposable amplicon containment device with an embedded vertical-flow DNA detection strip to detect the presence of HIV-1 amplicons. The vertical-flow DNA detection strip has a control line to validate the performance of the device as well as a test line to detect the analyte. The analyte is detected by a sandwich immunoassay for reporter moieties on a capture probe and a detection probe. The control line consists of the detection probe reporter moiety conjugated to the vertical-flow DNA detection strip. The preliminary limit of detection of the IsoAmp HIV assay was evaluated by testing serial dilutions of the HIV-1 Armored® RNA (Assuragen, Austin TX). We found that twenty-one out of twenty-eight (75%) assays were positive when 50 copies of the HIV-1 Armored RNA were input into the IsoAmp HIV reaction.